Multiculturalism in Germany: results, problems and prospects (Journal of Philosophy Culture and Political Science, 2015)
This article discusses the features of the development of multiculturalism in Germany. In particular, for a long time the official German authorities pursued a policy of not recognizing the political rights of migrant workers and their descendants. At the initial stage, the German government considered «guest workers» as an exclusively labor, and did not see them full members of German society. The country has no legal mechanisms to ensure full assimilation and naturalization of immigrants wishing to stay in the country on a permanent basis. In light of recent international events special emphasis in the article attached to the problems of integration of Muslim migrants. In conclusion, the authors give their own understanding of the issues of multiculturalism in Germany.Key words: migration, «guest workers», multiculturalism, integration, ethnic enclaves, a parallel society, identity.